System of control of temperature for a reaction of Saponification in a continuous - Collado Domínguez, Emerson (2005)
The technological progress achieved, especially regarding to computerized control systems, are facilitating the chemical engineer a better understanding and control of a larger number of variables, restrictions and specifications that are involved in a determinate process, making them more efficient and allowing to obtainhigher performances, without compromising the product's quality and the production levels that are required. The purpose of the control system suggested is to maintain the desired temperature value for a chemical reaction in order to obtain the best conversion as possible, in presence of disturbances that occur while the process is taking place, and are associated with the flow and concentrations of the reactants and also withthe flow and temperature of the saturated heating steam. From the mathematical model presented in this article and the knowledge of other elements involved such as control valves, sensors, transmitters, and transducers, a SCADA system with the use of a PLC is able to supervise, monitor and control the chemical reaction in real time, keeping the temperature in its optimal desired value.